Comparison of Employee Workloads Partners of Pt. Telkom Bengkulu Region - Arif Rahman Danu Pratama; Ahmad Soleh; M. Rahman Febliansa (Focus of Human Resource Management Journal, 2026)
This study discusses the comparison of workload between partner employees of PT. Telkom Bengkulu, namely Trans Dana Profitri (Squad DEFA) and Mitratel (Squad BRAVO). Workload is understood as both physical and mental demands that must be balanced with employee capacity to maintain optimal performance. The differences in responsibilities between the two partners result in variations in workload levels, where supervisors and administrative staff often experience workloads above the standard, while technicians remain relatively within the standard. The research method used was descriptive quantitative, with data collected through observation, interviews, documentation, and questionnaires. The sample consisted of 36 respondents, comprising 24 employees from Mitratel and 12 employees from Trans Dana Profitri. The data were analyzed using data adequacy test, data uniformity test, Independent Sample t-Test, F-test, coefficient of determination (R²), and effective workload calculations based on standard working hours according to the Regulation of the Minister of Finance No. 175/PMK.01/2016. The results showed that the workload for supervisory and administrative positions reached 180%, which ideally should be handled by two employees but in practice is only performed by one person. Meanwhile, the workload of technicians was 110%, which is still within the acceptable standard. Overall, Trans Dana Profitri employees bear a heavier workload compared to Mitratel employees, as they are directly responsible for managing digital energy devices and network maintenance, which could cause widespread service disruptions (GAMAS) if not addressed. These findings emphasize the importance of redistributing workload and adding employees in overloaded positions to ensure efficiency and service quality at PT. Telkom Bengkulu.